Evaluation of squeezing pretreatment for improving methane production from fresh banana pseudo-stems. (1st February 2020) - Pan, Shiyou; Chi, Yue; Zhou, Lang; Li, Zhenchong; Du, Liqin; Wei, Yutuo
Highlights: High moisture content is a prominent feature of banana pseudo-stems (BPS). The effect of squeezing pretreatment on methane production from BPS was evaluated. Methane production increased by 41.2% after pretreating BPS by squeezing. Most phenols were lost with the BPS juice during squeezing. Energy output from squeezed BPS exceeded energy consumption during pretreatment. Abstract: Banana pseudo-stems (BPS) are an abundant and low-lignin-content lignocellulosic biomass for methane production. However, the high-water content in BPS increases the transport costs, and the resistant structure of BPS hinders methane production. In this study, squeezing of BPS as a pretreatment was evaluated for improving anaerobic digestion (AD). After 20-d digestion, methane production from squeezed BPS was 204.2 ± 6.2 mL/(g volatile solids (VS) of feedstock), which was 41.2% more than that from untreated BPS. This increase was mainly attributed to the improvement of physical properties (e.g. water absorbing capacity) and the change in the resistant structure of BPS after squeezing, which promoted good contact between microbes and substrate during AD. The measured methane production was described using a modified Gompertz model and the results showed that anaerobic process would take less time and occur faster when pretreated BPS was used as the substrate. The energy produced during AD of squeezed BPS, after deducting the energy used by the squeezer, resulted in an energy surplus of 26.2%.